Effects of one directional pneumatic tube system on routine hematology and chemistry parameters; A validation study at a tertiary care hospital - A-Jin Lee; Hun Suk Suh; Chang-Ho Jeon; Sang-Gyung Kim (Practical Laboratory Medicine, 2017)
Background: The validation of sample stability through pneumatic tube system (PTS) is essential. The objective of this study was to evaluate the effects of PTS transportation on laboratory results. Methods: Paired EDTA and SST blood samples were collected from 56 randomly selected patients. Laboratory parameters were compared between PTS group and hand-delivered group. Results: No statistical differences were observed for complete blood counts, white blood cell differential parameters, erythrocyte sedimentation rate and most chemistry parameters between PTS and hand-delivered transport procedures. Mean platelet volume results obtained from samples transported through PTS were lower than that obtained from samples transported through hand-delivered method (P = 0.001). The results of aspartate aminotransferase (P = 0.000), lactate dehydrogenase (P = 0.000), and hemolysis index (P = 0.000) from PTS group were higher than that from hand-delivered group. Conclusions: All laboratories should validate the stability of the results from samples according to transportation method. Keywords: Pneumatic tube, Courier, Transportation, Preanalytical phase, Quality